2016
DOI: 10.4103/0970-9185.175665
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of predictors of depth of the corner pocket for ultrasound-guided supraclavicular brachial plexus block

Abstract: Background and Aims:There is wide variation in depth of brachial plexus in patient population at supraclavicular region. We plan to find the depth of the corner pocket and correlate it with age, weight, height and body mass index (BMI).Material and Methods:After approval from Ethics Committee, right-sided supraclavicular region of volunteers was scanned. Once an optimal image, which included subclavian artery, pleura, first rib and nerve bundles, was obtained, the corner pocket was kept in the middle of the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…[ 9 ] Significant correlations have been observed between weight, BMI and the depth of corner pocket in a study on Indian population. [ 4 ] We also found significant correlation between the weight, BMI and SD and LD between skin and the neural element.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[ 9 ] Significant correlations have been observed between weight, BMI and the depth of corner pocket in a study on Indian population. [ 4 ] We also found significant correlation between the weight, BMI and SD and LD between skin and the neural element.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, USG predictors of corner pocket depth have been studied for USG-guided supraclavicular block in Indian population. [ 4 ] However, to the best of our knowledge, there was no study where the variability of depth of the neural elements of brachial plexus in supraclavicular area had been assessed with ultrasound in Indian population. Hence, this study was conceived to give some approximation of the depth of the brachial plexus from the skin.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, they have tried to correlate plexus depth in supraclavicular fossa with body mass index of Indian patients so as to avoid pleural puncture. [ 19 ] Brachial plexus is quite superficial superiorly in interscalene groove,[ 20 ] as it courses downward behind clavicle, it is deep. In a magnetic resonance image-based study, skin to nerve distance was reported to vary from 1.8 to 4.5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The corner pocket is located between the first rib or the pleura inferiorly, the subclavian artery medially, and the inferior trunk of the supraclavicular brachial plexus superiorly. 4 This approach is preferred for brachial plexus nerve block because of its ulnar sparing property. 5 This procedure can be performed using the blind anatomical palpation method combined with the application of a nerve stimulator.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that BMI is positively correlated with the depth of the corner pocket when measured from the skin. 4 In other words, as BMI increases, the distance from the skin to the corner pocket increases. In this study, stroke patients with upper limb spasticity and CRPS were recruited for ultrasound-guided supraclavicular brachial plexus nerve block.…”
Section: Introductionmentioning
confidence: 99%